THE MISHING OF ASSAM- A QUESTION OF ETHNIC IDENTITY - Dr Birinchi Kr. Bora (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Assam is situated in the northeast part of the country. The north eastern region is comprises with eight states of north east part and Assam is its nerve centre. Tribal situation of Assam is in critical juncture because of different identity assertions of ethnic and tribal groups .Mishings are the second largest group of a scheduled tribes in Assam. They have their own distinctive identity. There are lots of basic causes of identity crisis of Mishings of Assam. This paper attempt to highlight the several issues of identity crisis among the Mishings in Assam in particular and the tribes of Assam in general.